Exploring the Neglect of Accounting Theory in Current Academic Research in Nigeria - Augustine E., Osho; Ramat A, Omolola (European Scientific Journal, ESJ, 2018)
It has become a general perception that studies in Accounting Theory, though an essential part of accounting research is gradually becoming extinct. While globally, there is a dearth of studies and researches on accounting theory, in Nigeria, such studies are literally almost nonexistent. Hence, the motivation for this study to explore the neglect of accounting theory in current academic research in Nigeria. To achieve the objectives of this study, the researchers employed case study method of research, adopting the Department of Accounting, in one of the private Universities in Nigeria as a study area. Analyzing the result of the survey, critical findings revealed among others, that factors such as Methodology, Social, Resources, Technology and Regulatory issues are the causes of neglect of accounting theory in Nigeria’s Academic Area. It is recommended among others that there should be development of electronic databases of accounting researches to ease the data gathering difficulties, as well as making research and seminars in accounting theory compulsory for accounting students to stimulate interest in accounting theory in other to develop capacity and avoid extinction.